2019
DOI: 10.3390/ma12233956
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen on Martensite Transformations and the State of Hydrogen Atoms in Binary TiNi-Based Alloy with Different Grain Sizes

Abstract: The analysis presented here shows that in B2-phase of Ti49.1Ni50.9 (at%) alloy, hydrogenation with further aging at room temperature decreases the temperatures of martensite transformations and then causes their suppression, due to hydrogen diffusion from the surface layer of specimens deep into its bulk. When hydrogen is charged, it first suppresses the transformations B2↔B19′ and R↔B19′ in the surface layer, and when its distribution over the volume becomes uniform, such transformations are suppressed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Hydrogen absorption is enhanced owing to the high hydrogen solubility limit and diffusion rate in the martensite phase [41]. Moreover, hydrogen absorption is further enhanced by dynamic lattice changes due to transformation [44,45,[48][49][50][51]. Nevertheless, it is likely that the present countermeasure for hydrogen absorption is effective because of the inhibition of hydrogen evolution, although corrosion resistance somewhat decreases in the presence of the martensite phase or during martensite transformation.…”
Section: Inhibition Of Hydrogen Absorptionmentioning
confidence: 99%
“…Hydrogen absorption is enhanced owing to the high hydrogen solubility limit and diffusion rate in the martensite phase [41]. Moreover, hydrogen absorption is further enhanced by dynamic lattice changes due to transformation [44,45,[48][49][50][51]. Nevertheless, it is likely that the present countermeasure for hydrogen absorption is effective because of the inhibition of hydrogen evolution, although corrosion resistance somewhat decreases in the presence of the martensite phase or during martensite transformation.…”
Section: Inhibition Of Hydrogen Absorptionmentioning
confidence: 99%
“…By now, hydrogen's effect on MT has been studied mainly on TiNi polycrystals [1,[3][4][5][6][7][8][22][23][24][25][26]. These studies have shown that hydrogen's effect on the mechanical and functional properties is determined by the state of hydrogen in the initial B2 phase (as metal hydrides or atoms in a solid solution), its concentration, and the type of initial phase itself (austenite or martensite) upon hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…At low concentrations below 400 wppm (wppm represents weight part per million), hydrogen contributes to an increase in the plasticity of the martensite phase and superelasticity. When hydrogen concentrations are greater than 400 wppm, hydrogen reduces plasticity; suppresses shape memory; and in TiNi alloys with a one-stage B2-B19 MT, induces the R phase through stresses [1,[3][4][5][6][7][8][9][10][22][23][24][25][26]. Nevertheless, despite numerous experimental data, interest in studying the effect of hydrogen on the functional properties of binary TiNi alloys remains due to their wide use in the dental and medical fields [11,18,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the in situ investigation of the defect structure evolution during hydrogen exposure is more useful in terms of the mechanisms of hydrogen embrittlement. Experiments on the hydrogen interaction with materials are carried out either using the liquid phase (electrolytic saturation) [14] or gas phase (hydrogen gas sorption at high pressure and various temperatures) [15]. These conditions impose more stringent requirements for the potential positron sources to be used for in situ studies.…”
Section: Introductionmentioning
confidence: 99%